(untitled) (Asian Journal of Medical and Biological Research, 2023)
The treatment of alopecia is widely available, and numerous studies have been conducted for its improvement. However, research focusing on the Bangladeshi population is extremely rare. A number of dermatology clinics in Bangladesh are providing advanced treatment; therefore, the efficacy of those treatments needs to be assessed. The aim of this study was to determine the pattern of alopecia in Bangladesh and identify the factors that are associated with poor treatment responses to administered therapies. We conducted a cross-sectional study among alopecia patients who were getting treatment at Aurora Skin and Aesthetics and completed at least six sessions under an experienced physician. Interviews run by experienced physicians collected demographic, clinical, treatment, and comorbidity-related information from patients aged between 18 and 65 years. The collected data were analyzed using STATA (version 16.0). Among our participants, male pattern baldness (stage-2) was most common (43.6%), followed by male pattern baldness (stage-3) (18.8%) and female pattern hair loss (FPHL), stage-2 (13.9%). The treatment efficacy was good for 46.5% of patients, medium for another 42.56%, and only 10.9% showed poor efficacy. The oily hair of participants showed a statistically significant negative association with treatment efficacy (P=0.018). The presence of chronic disease and stress among alopecia patients also negatively impacts the treatment process (P<0.05). Smoking among alopecia patients also hampers the treatment process and is significantly associated with poor treatment efficacy. From this study, it is clear that the ongoing treatment has overall excellent efficacy; however, attention should be given to the comorbidities and habits of patients to improve the treatment outcome. The findings of this study would help skin specialists make decisions during alopecia treatment. Asian J. Med. Biol. Res. 2023, 9 (4), 106-113